Iodide based polyamide stabilisers as potential risk for corrosion in electronics. (1st September 2013) - Leineweber, M; Müller, L
Abstract : Microelectronic devices consist of a number of corrosion sensitive metallic combinations such as gold-aluminium and zinc coated steel. Polyamides (PAs) are well known packaging materials for microelectronic devices such as integrated circuits. Iodide based stabilisers are used in PA, and degassing of the iodine from the packaging materials can introduce significant corrosion problems on the microcircuit assembly. The investigations in this paper focus on the effect of iodine containing PA stabilisers on the corrosion of zinc coated steel parts and gel protected gold-aluminium wire bond connections, and elucidation of the corrosion mechanisms.